"Some uninteresting data from a faraway country": Inequity and coloniality in international social psychological publications. (5th December 2021) - Bou Zeineddine, Fouad; Saab, Rim; Lášticová, Barbara; Kende, Anna; Ayanian, Arin H.
Abstract: Modern systems of knowledge production reinforce inequalities and coloniality, especially in the Global South. We investigated whether this was the case in contemporary social psychology. We examined manifestations of coloniality of knowledge (in the form of internalized Global North standards and practices) and critical awareness and reflection (historic and systemic attributions for collective disadvantages) in a survey of social psychologists in 64 countries ( N = 232). Although colleagues in the Global South and Southern and Eastern Europe adopted Global Northern publication standards and tendencies, their compliance seemed motivated by institutional demands and pragmatic concerns rather than internalized inferiority or principled conviction. Regarding international mainstream publication practices, participants from all regions (most prominently outside the Global North) reported biases, under‐representation, lack of relevance, and structural disadvantages. Participants offered mainly systemic attributions for these and other disadvantages. These findings suggest that social psychologists engaged with the international publication system are caught in a double‐bind between collective systemic disadvantages and coerced compliance, especially outside the Global North. Discussion focuses on the mixed‐motive tensions these social psychologists experience in publishing internationally under these conditions, and the implications of this status quo for knowledge production in the discipline.